2016
DOI: 10.1177/1476127016633335
|View full text |Cite
|
Sign up to set email alerts
|

Laying a smoke screen: Ambiguity and neutralization as strategic responses to intra-institutional complexity

Abstract: Our research contributes to knowledge on strategic organizational responses by addressing a specific type of institutional complexity that has, to date, been rather neglected in scholarly inquiry: conflicting institutional demands that arise within the same institutional order. We suggest referring to such type of complexity as “intra-institutional”—as opposed to “inter-institutional.” Empirically, we examine the consecutive spread of two management concepts—shareholder value and corporate social responsibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 182 publications
0
71
0
3
Order By: Relevance
“…Given its early centrality to institutional accounts, it is not surprising that this theme has attracted '[v] What is notable from their review is that, although our understanding of these issues has significantly advanced, there are still many gaps and confusions. More recent research has begun to address what happens after adoption -to the practices that diffuse (e.g., Ansari, Fiss, & Zajac, 2010;Gehman, Trevino, & Garud, 2013) or the organizations (e.g., Weber, Davis, & Lounsbury, 2009), or how the adoption of practices influences future decisions depending on whether the practices enact the same or competing institutional logics (Meyer & Höllerer, 2016;Shipilov, Greve, & Rowley, 2010). There is, too, growing interest in how 'controversial or counter-normative' practices diffuse (or not).…”
Section: Diffusion and Isomorphismmentioning
confidence: 99%
“…Given its early centrality to institutional accounts, it is not surprising that this theme has attracted '[v] What is notable from their review is that, although our understanding of these issues has significantly advanced, there are still many gaps and confusions. More recent research has begun to address what happens after adoption -to the practices that diffuse (e.g., Ansari, Fiss, & Zajac, 2010;Gehman, Trevino, & Garud, 2013) or the organizations (e.g., Weber, Davis, & Lounsbury, 2009), or how the adoption of practices influences future decisions depending on whether the practices enact the same or competing institutional logics (Meyer & Höllerer, 2016;Shipilov, Greve, & Rowley, 2010). There is, too, growing interest in how 'controversial or counter-normative' practices diffuse (or not).…”
Section: Diffusion and Isomorphismmentioning
confidence: 99%
“…An example for such a case, within one sector of the sharing economy, is the regulation of commercial actors (such as Uber) while partnering with noncommercial actors (for instance, with private peer-to-peer car sharing initiatives). Meyer and Höllerer (2016) describe this as 'intra-institutional' complexity (as opposed to 'interinstitutional') and emphasize ambiguity as way to deal with such complexity. In addition, heterogeneous responses can also origin from different subunits of the city administration being confronted with different demands from their environment (Binder 2007), such as the planning department of a city versus the tax office.…”
Section: Heterogeneity In the Combination Of Public Governance Stratementioning
confidence: 99%
“…In this way, we address the concerns of scholars who contend that management concepts should not be analysed in isolation but are linked to each other in various ways (e.g. Abrahamson & Fairchild, 1999;Meyer & Höllerer, 2016;Shipilov et al, 2010). We build on and extend such literature by suggesting a conceptual framework that (a) covers a whole population of management concepts, and (b) allows us to disentangle direct and indirect relationships between management concepts and study their implications for theorization.…”
Section: Implications For Research On Theorizationmentioning
confidence: 99%
“…Existing research in this area has suggested that management concepts exhibit distinct relationships to each other (e.g. Abrahamson & Fairchild, 1999;Meyer & Höllerer, 2016;Shipilov et al, 2010) and are also embedded in broader discourses or myths of modernity (e.g. Chreim, 2006;Shenhav, 1999;Zeitz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%